Pola pikir berkembang dan perilaku kerja inovatif: Menguji peranan kepemimpinan berbasis kekuatan dan iklim inovasi: Growth mindset and innovative work behavior: Examining the role of strengths-based leadership and innovation climate - Osi Isna Sabela; Arum Etikariena (Persona:Jurnal Psikologi Indonesia, 2025)
The government continues to promote public sector transformation to have maximum impact. Civil Servants as policy implementers need to be adaptive in innovating according to the core values ​​of Ber-AKHLAK. The uniqueness of the public sector shows the urgency of examining its innovative work behavior. This study aims to investigate the effect of growth mindset on innovative work behavior with simultaneous moderation of strength-based leadership and innovation climate using Self Determination Theory (SDT). ). A cross-sectional self-report survey using the innovative work behavior scale (α=0.97), the growth mindset scale (α=0.90), the strengths-based leadership scale (α=0.95), and the innovation climate scale (0.91) involved 179 civil servants at agency X who play a vital role in managing employees. PROCESS Macro Model 2 in SPSS shows that growth mindset has a direct positive and significant effect on innovative work behavior. However, strength-based leadership and innovation climate simultaneously do not significantly moderate it. From a SDT perspective, growth mindset directly motivates civil servants’ innovative work behavior by fulfilling their basic psychological needs for autonomy, competence, and relatedness. Government organizations can focus on fostering a growth mindset in civil servants rather than disseminating strength-based leadership practices and innovation climate.